الأمراض والطب في حضارتي بلاد الرافذ ينً ومصر - كديدة,مسعود; الأخوص,حمزة; شيخة بلقاسم,يوسف (University of Eloued جامعة الوادي, 2024)
- الملخص: تطرقنا في هذا العمل إلى لمحة وجيزة ومختصرة في موقع وجغرافية بلاد الرافدين ومصر القديمة وأهم التضاريس البيئية والتربة والأنهار والمناخ المساعد لهم، ولقد القينا نظرة مختصرة حول مفهوم المرض ومختلف الأمراض التي كانت سائد وأهم الأسباب التي أدت إلى المرض وانتشاره كما حاولنا تقديم شرح مختصر حول الطب والعلاج في بلاد الرافدين تاريخ وتقدم الطب عند السومرين والأكديين ثم البابليين والآشوريين وكيفية صناعة العقاقير والأدوية المستخلصة من الأعشاب النباتية والحيوانية ودور الطبيب والوصفات الطبية في الشفاء. وتطرقنا باختصار الى نظرة المصريين للمرض كما عرضنا أسباب وأنواع المرض في مصر القديمة وشرحنا مهنة الطبيب عند المصريين وطريقة التشخيص والعلاج عندهم التي تمر بمراحل لعلاج المريض وبعد ذلك طريقة تحضير الوصفات الطبية والعقاقير سواء نباتية أو حيوانية. • Abstract : In this work, we touched upon a brief and brief overview of the location and geography of Mesopotamia and ancient Egypt and the most important environmental terrain, soil, rivers and the climate conducive to them.we took a brief look at the concept of disease and the various diseases that were prevalent and the most important causes that led to the disease and its spread. we also tried to provide a brief explanation about medicine and treatment in Mesopotamia, the history and progress of medicine among the Sumerians, Akkadians, Babylonians and Assyrians, how to make drugs and medicines extracted from plant and animal herbs, the role of the doctor and prescriptions in healing.We briefly touched upon the Egyptians ' view of the disease, we also presented the causes and types of disease in ancient Egypt, we explained the profession of a doctor among the Egyptians, the method of diagnosis and treatment, which goes through stages to treat the patient, and then the method of preparing prescriptions and drugs, whether plant or animal.
Keywords: treatment; diagnosis; علاج; تشخيص